Cross-Sectional Study to Characterise Nicotine Dependence in Central Vietnamese Men. (January 2019) - Kõks, Gea; Tran, Ha Diep Thi; Ngo, Ngoc Bich Thi; Hoang, Linh Nhat Nguyen; Tran, Hue Minh Thi; Ngoc, Thanh Cao; Phuoc, Thuoc Doan; Dung Ho, Xuan; Duy, Binh Ho; Lättekivi, Freddy; Kõks, Sulev
Tobacco is legally permitted for adults, easily available, and the prevalence of smoking is high. Tobacco use is the largest preventable risk factor for human disease. To reduce smoking, many countries have introduced public policy to restrict the distribution of tobacco. The aim of this study was to analyse tobacco smoking and nicotine dependence in Central Vietnamese men around Hue and Da Nang cities. Nicotine dependence was measured using the Fagerström Test for Nicotine Dependence (FTND) score. The cohort contained total of 1822 Central Vietnamese men from Hue and Da Nang: 1453 smokers and 369 non-smokers. Individuals completed a questionnaire and factors such as smoking initiation, quitting behaviour, and success in quitting were also recorded. In the smoking group, the average amount of time in which the individual had smoked was 26.4 years. Average FTND value was 4.02, median was 4, the first quartile was 2, and the third quartile was 6. In all, 431 smokers (30%) had an FTND score of 6 or higher; an FTND score of this value is considered to equate to an individual having high nicotine dependence. Therefore, it could be noted that high nicotine dependence is very common in Central Vietnam. High nicotine dependence was significantly correlated with years of smoking. The longer the smoking period, the higher the FTND score. A high FTND score correlated with the individual being less likely to successfully quit smoking. The results of the questionnaire demonstrate that even when there is no restriction in public policy concerning the distribution of tobacco, individuals still wish to quit smoking. This study identified a high prevalence of severe nicotine dependence in Central Vietnamese men and the majority smokers wished to quit smoking. Consequently, the results of this study highlight the acute need for a specific programme to aid smokers in Central Vietnam to quit smoking.